Effect of cholecystectomy on bowel function: a prospective, controlled study. Issue 6 (1st December 1999) - Hearing, S D; Thomas, L A; Heaton, K W; Hunt, L
Abstract : BACKGROUND: Published estimates of the prevalence of postcholecystectomy diarrhoea derive from retrospective or uncontrolled data. They ignore functional bowel syndromes and possible changes in diet and drug use. AIMS: To determine prospectively whether and how often cholecystectomy leads to changes in bowel function and bowel symptoms, especially to liquid stools, over and above any non-specific effect of laparoscopic surgery. SUBJECTS: Patients: 106 adults undergoing laparoscopic cholecystectomy (85 women, 21 men). Controls: 37 women undergoing laparoscopic sterilisation. METHODS: Before and 2–6 months after surgery patients were administered questionnaires about bowel frequency, bowel symptoms, diet, and drugs, and kept records of five consecutive defecations with assessment of stool form or appearance on a seven point scale. RESULTS: In cholecystectomised women, stated bowel frequency increased, on average by one movement a week, and fewer subjects felt that they became constipated. However, records showed no consistent change in bowel frequency, stool form, or defecatory symptoms. Six women reported diarrhoea after the operation but in only one was it clearly new and in her it was mild. Change in dietary fibre intake did not associate with change in bowel function but stopping constipating drugs did in a minority. In women being sterilised there was no consistent change in bowel function. In men having cholecystectomy no consistent changes were observed. CONCLUSIONS: In women, cholecystectomy leads to the perception of less constipation and slightly more frequent defecations but short term recordings show no consistent change in bowel function. Clinical diarrhoea develops rarely and is not severe.